Concomitant Sjögren's Syndrome Was Not Associated with a Poorer Response or Outcomes in Ursodeoxycholic Acid-Treated Patients with Primary Biliary Cholangitis - Ni, Ping (Can J Gastroenterol Hepatol, 2019)
AIM: Patients with primary biliary cholangitis (PBC) have at least 60% probability of having an autoimmune extrahepatic condition, with the most common being Sjögren's syndrome (SS). The impacts of SS on the response and outcomes in ursodeoxycholic acid (UDCA)-treated patients with PBC, however, remain unclear. The aim of this study was to document the biochemical responses and clinical outcomes of UDCA-treated patients with concomitant SS and to compare the findings to those of patients with PBC alone. METHODS: Data from consecutive patients with PBC who visited West China Hospital affiliated with Sichuan University between October 2013 and October 2017 were reviewed retrospectively. RESULTS: The study populations consisted of 226 patients with PBC alone and 56 with PBC/SS. The median ages, proportions of female patients, Fib-4 scores, and aspartate aminotransferase (AST)/platelet ratio index (APRI) at baseline in the two cohorts were similar. At presentation, patients with PBC/SS had higher serum IgG levels and positive rates for serum antinuclear antibody (ANA) than patients with PBC alone (all P < 0.05). There was no statistically significant difference between the rate of biochemical response to UDCA at 1 year in the PBC/SS and PBC alone groups. The UK-PBC risk scores and GLOBE scores in UDCA-treated patients in the two cohorts were also similar. During the follow-up period, the differences in the liver enzyme levels, Fib-4 scores, APRI, and incidence of liver-related adverse events were not significant. CONCLUSIONS: The results of this retrospective, single-center study suggest that the response and clinical outcomes of UDCA-treated patients with PBC are not adversely affected by concomitant SS.